Institutional practices and planning for walking: A focus on built environment audits - Babb, Courtney; Curtis, Carey (2015)
Built environment audits, part of the “toolbox” for planning multi-modal urban transport systems, are used to evaluate the walkability of streets. Whereas the methodological features of audits have attracted attention from planning research, little attention has been paid to the institutional contexts where audits are developed and used. Drawing on literature on audit culture in contemporary institutions and on expert interviews with audit developers and professionals in Australia and New Zealand working with walking audits, three questions are addressed: Who uses walkability audits? How are they used? What substantive changes emerge from auditing practice? The knowledge of practice of auditing the built environment for walking is underdeveloped. While planners, engineers and advocates consider built environment audits useful in different ways, of concern is the use of audits to rationalise limited resources already devoted to infrastructure for walking, rather than produce substantive changes to the quality of the built environment for walking.